2022
DOI: 10.1002/jmv.28334
|View full text |Cite
|
Sign up to set email alerts
|

Application of nested multiplex polymerase chain reaction respiratory and pneumonia panels in children with severe community‐acquired pneumonia

Abstract: Community‐acquired pneumonia (CAP) is a serious clinical concern. A lack of accurate diagnosis could hinder pathogen‐directed therapeutic strategies. To solve this problem, we evaluated clinical application of nested multiplex polymerase chain reaction (PCR) in children with severe CAP. We prospectively enrolled 60 children with severe CAP requiring intensive care between December 2019 and November 2021 at a tertiary medical center. Nested multiplex PCR respiratory panel (RP) and pneumonia panel (PP) were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Positive BioFire results with negative bacterial culture may be related to multiple factors: low count of the isolate on culture plates compared to the cut-off which is therefore not reported, unavailability of culture media that support growth of fastidious bacteria, PCR may detect non-viable organisms, in addition to the antibiotic misuse which may inhibit growth on culture media, also the fact that the count released by BioFire is in the form of copies/ml which is greater when compared to the culture count in the form of CFU/ml [16]. This was discordant with Ginocchio et al who stated that the positive BioFire results (70.6%) were mainly bacterial (20.5%) rather than viral targets (2.9%) and Yen et al who stated that the three most common bacteria detected were S. aureus, Streptococcus pneumoniae, and Moraxella catarrhalis [11,13]. Also, Debbagh et al found that bacterial etiology was the most common (69.3%), represented mainly by M. catarrhalis (11.4%), followed by viral etiology (30.7%), with HR/EV as the most prevalent [18].…”
Section: Pathogens Detected Using Biofire Filmarraymentioning
confidence: 74%
See 3 more Smart Citations
“…Positive BioFire results with negative bacterial culture may be related to multiple factors: low count of the isolate on culture plates compared to the cut-off which is therefore not reported, unavailability of culture media that support growth of fastidious bacteria, PCR may detect non-viable organisms, in addition to the antibiotic misuse which may inhibit growth on culture media, also the fact that the count released by BioFire is in the form of copies/ml which is greater when compared to the culture count in the form of CFU/ml [16]. This was discordant with Ginocchio et al who stated that the positive BioFire results (70.6%) were mainly bacterial (20.5%) rather than viral targets (2.9%) and Yen et al who stated that the three most common bacteria detected were S. aureus, Streptococcus pneumoniae, and Moraxella catarrhalis [11,13]. Also, Debbagh et al found that bacterial etiology was the most common (69.3%), represented mainly by M. catarrhalis (11.4%), followed by viral etiology (30.7%), with HR/EV as the most prevalent [18].…”
Section: Pathogens Detected Using Biofire Filmarraymentioning
confidence: 74%
“…FilmArray testing (BioFire Diagnostics, LLC, Salt Lake City, UT, USA) Sample collection: ETA or BAL was collected from children who were intubated or underwent bronchoscopic examination. For other children, sputum samples were collected from children unless they were not able to expectorate, and a nasopharyngeal swab (NPS) was collected [11]. The NPS was immediately placed in viral transport media (VTM) (Disposable virus sampling swab kits, Bioteke corporation, Wuxi, Co., Ltd., China), sputum, ETA and BAL samples were collected in sterile containers.…”
Section: Sample Processingmentioning
confidence: 99%
See 2 more Smart Citations